Familial patterning and prevalence of male androphilia among Istmo Zapotec men and muxes. - Francisco R Gómez (PLoS ONE, 2018)
Male androphilia (i.e., male sexual attraction to other adult males) is known to cluster within families. Some studies demonstrate that male androphilia clusters in both the paternal and maternal familial lines, whereas other studies demonstrated that it clusters only in the latter. Most of these studies were conducted in Euro-American populations where fertility is low and the sexual orientation of male relatives can sometimes be difficult to ascertain. These two factors can potentially confound the results of such studies. To address these limitations, we examined the familial patterning of male androphilia among the Istmo Zapotec of Oaxaca, Mexico--a high fertility, non-Euro-American population where androphilic males are known locally as muxes, a third gender category. The Istmo Zapotec recognize two types of muxes--muxe gunaa and muxe nguiiu--who typify the transgender and cisgender forms of male androphilia, respectively. We compared the familial patterning of male androphilia between muxe gunaa and muxe nguiiu, as well as between gynephilic men and muxes (both cisgender and transgender forms combined). Istmo Zapotec muxe gunaa and muxe nguiiu exhibit similar familial patterning of male androphilia. Overall, muxes were characterized by significantly more muxe relatives than gynephilic men. This familial patterning was equivalent in both the paternal and maternal lines of muxes. The population prevalence rate of male androphilia was estimated to fall between 3.37-6.02% in the Istmo Zapotec. This is the first study that has compared cisgender and transgender androphilic males from the same high fertility population and demonstrated that the two do not differ with respect to the familial patterning of male androphilia.